2021
DOI: 10.3390/ijerph182010959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Government Subsidies on Production and Emissions Reduction Decisions under Carbon Tax Regulation and Consumer Low-Carbon Awareness

Abstract: To promote low-carbon production, the government simultaneously provides some subsidies under carbon tax regulations. Two government subsidies are widely adopted: one is based on emissions reduction quantity and the other is based on emissions reduction investment cost. Additionally, consumer low-carbon awareness has also been enhanced. Considering the aforementioned circumstances, this paper investigates the effects of different government subsidies on production and emissions reduction decisions under a carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
2
8
0
1
Order By: Relevance
“…Most of the above literature only considers a single carbon policy or compares the effects of different carbon policies. For mixed carbon policy, scholars often study carbon subsidies in combination with the other two policies [ 37 , 38 , 39 ]. Few scholars study the hybrid policy combination of carbon trading and carbon tax, which are becoming important lately [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the above literature only considers a single carbon policy or compares the effects of different carbon policies. For mixed carbon policy, scholars often study carbon subsidies in combination with the other two policies [ 37 , 38 , 39 ]. Few scholars study the hybrid policy combination of carbon trading and carbon tax, which are becoming important lately [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for incentive-punishment policies, more literature focused on the effect of government subsidies on carbon abatement investment decisions [ 5 , 12 , 38 , 39 ]. There are also a few studies concerned with the relationship between the government reward-punishment mechanism and low-carbon abatement activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lastly, this section further explores the effect of the carbon tax rate and the reward-punishment coefficient on the government’s optimal pre-determined carbon abatement target, the manufacturer’s abatement investment level, and the excessive abatement level. Referring to [ 39 ] and combined with an actual situation in practice, we set the base parameters as follows. For instance, parameter λ was equal to 0.2 ( λ = 0.2), which represents consumers’ preference degree for low-carbon products.…”
Section: Government’s Optimal Decisionsmentioning
confidence: 99%
“…Wang et al [63] confirmed that manufactured can offset the negative economic impact of the carbon emission tax policy by making low carbon emission technology investment. Wang et al [64] investigated the different government subsidies on production and emission reduction decisions under a carbon tax regulation by formulating three optimization models.…”
Section: Carbon Tax Policy Of Clscmentioning
confidence: 99%